Facile synthesis of CoX (X = S, P) as an efficient electrocatalyst for hydrogen evolution reaction1. Issue 24 (28th June 2015) - Li, Jiayuan; Zhou, Xuemei; Xia, Zhaoming; Zhang, Zhiyun; Li, Jing; Ma, Yuanyuan; Qu, Yongquan
<x xml:space="preserve">Abstract</x> HER catalytic activity of CoX (X = S, P) nanocatalysts prepared through a facile and controllable synthesis by the chemical conversion of thin Co(OH)2 nanoplates was studied. The better HER performance of CoP could be derived from its intrinsically positive charged nature of the metal center Co, the long bond length of Co–P and the abundant catalytic active sites toward HER.